FOLIC ACID DEPHYCYTE IN FERTILE WOMEN WITH GASTROINTESTINAL DISEASES - Narmetova M.U; Makhmudova A.D; Suleymanova D.N (Scholar Express Journals, 2022)
To study some risk factors for folic acid deficiency in adolescent girls and women of childbearing age. 150 adolescent girls of 12-18 years old and 96 women of childbearing age who were on a regular basis with various gastrointestinal pathologies. In patients with chronic gastrointestinal diseases and chronic hepatitis, FC indicators are significantly reduced, compared with healthy ones 9.15±0.16 ng/ ml and 13.23±0.32 ng/ml, respectively (p<0.01). Folic acid indices in those examined with helminthiases (enterobiosis, giardiasis, hymenolepidosis, ascariasis) and without helminthiases do not significantly differ 11.95±0.26 ng/ml and 12.13±0.23 ng/ml, respectively (p>0, 05). A significant difference in the indicators of folic acid was found in patients daily consuming greens, legumes, fortified flour, compared with those who rarely consume them 12.73±0.18 ng/ml and 8.11±0.20 ng/ml, respectively (p<0.01)
Keywords: Folic acid; risk factors; women of fertile age; adolescent girls